Complete resection of pulmonary artery hemangioma on the beating heart. Issue 8 (25th March 2021) - Atta, Sameh; Verdichizzo, Danilo; Taberham, Rhona; Stavroulias, Dionisios; Kourliouros, Antonios
Abstract: Cardiac hemangiomas are rare entities and very few cases have been reported where they originate from the main arteries of the heart. We present a case of hemangioma arising from the main pulmonary artery, which was completely resected with clear margins on the beating heart.